2013
DOI: 10.3892/mmr.2013.1735
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor γ2 Pro12Ala (rs1801282) polymorphism and breast cancer susceptibility: A meta-analysis

Abstract: Abstract. Several studies have investigated the correlation between the peroxisome proliferator-activated receptor γ2 (PPAR-γ2) Pro 12 Ala (rs1801282) polymorphism and the risk of breast cancer, with inconsistent results. For this reason, a meta-analysis was conducted to identify the potential correlation after pooling data from eligible case-control studies. Search strategies were conducted in PubMed, EMBASE and the COCHRANE Library in English and from VIP, CNKI and Sinomed in Chinese (all the papers were pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…This polymorphism has an estimated frequency of 0.12 in a random Caucasian population [55]. This Pro12Ala substitution is associated with an increased incidence of colorectal cancer and breast cancer [56,57]. However, in investigating this Pro12Ala in PC, this polymorphism is not associated with increased PC risk or more aggressive disease [58].…”
Section: Pparγ Alterations In Prostate Cancermentioning
confidence: 99%
“…This polymorphism has an estimated frequency of 0.12 in a random Caucasian population [55]. This Pro12Ala substitution is associated with an increased incidence of colorectal cancer and breast cancer [56,57]. However, in investigating this Pro12Ala in PC, this polymorphism is not associated with increased PC risk or more aggressive disease [58].…”
Section: Pparγ Alterations In Prostate Cancermentioning
confidence: 99%
“…However, until this moment, studies investigating the association between PPARγ polymorphism and the risk of BC reported inconclusive results (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Several SNPs in the PPARG gene have been discovered, and rs1801282 (Pro12Ala), with a minor allele frequency (MAF) of 0.07 (based on information from 1000 genome project), is the most studied one ( 16 , 17 ). Another polymorphism located in PPARG , rs3856806 (His449His), is a frequent PPARG synonymous/3′-untranslated region (3′-UTR) polymorphism (MAF = 0.127) ( 17 ).…”
mentioning
confidence: 99%